Synthesis of Mesoporous g-Al2O3 Templated with Rosin-Based Quaternary Ammonium Salt by Ammonia Precipitation - Wang, Peng; Zhao, Zhendong; Bi, Liangwu; Chen, Yuxiang (Asian Journal of Chemistry, 2012)
Mesoporous alumina were successfully synthesized by a facile method of ammonia precipitation with rosin-based quaternary ammonium salt. Their structures were characterized with X-ray diffraction, N2 adsorption and desorption, transmission electron microscopy and thermal gravimetry-differential scanning calorimetry. The boehmite phase was achieved for precursors by ammonia precipitation, so that g-Al2O3 was easily prepared after the calcination at 550 ºC for 4 h. These calcined materials possessed wormhole-like mesopores without long range packing order but with a fairly uniform pore size. The rosin-based quaternary ammonium salt dosage and aging temperature had great impact on the properties of the alumina. When the dosage of rosin-based quaternary ammonium salt was 1.6 g and the aging temperature was 90 ºC, the maximum BET surface area (271 m2 g-1), pore volume (0.59 cm3 g-1) and pore size (6.39 nm) were obtained.